The relations between Scenic Space and Lighting at the turn of the 19th to the 20th century: The performativity in Appia's rhythmic space (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
The aesthetic proposals of the turn of the 19th to the 20th century around the explosion of scenic space, will guide the work of modern stage directors who, questioning the Italian scenic structure, invest in studies on the spatiality discovered by lighting. In this context, I develop an initial reflection about the concept of theatricality brought to the scenography and on its performativity traits, inaugurated by the experiments of Adolphe Appia, mainly with regard to the creation of what the director will call “Rhythmic Spaces”, resulting from his contact with the studies on rhythmics by Émile Jacques Dalcroze.
Keywords: scenic space; stage lighting; scenography; Appia